Bantuan Teknis Profesional Pengembangan Kurikulum Kepada Tim Pengembang Kurikulum Daerah Sebagai Wahana Pemberdayaan Staf Pusat Kurikulum - Sutjipto Sutjipto (Jurnal Pendidikan dan Kebudayaan, 2011)
This study set out to get a view of empowerment Curriculum Center staff through a strategy of professional technical assistance activities in the area of curriculum development. Methods This study is descriptive, where the main data is processed based on program activities, implementation activities, and report the results of activities Curriculum Center between 2006 through 2010 related to the professional technical assistance to the TPK provincial curriculum development in 33 provinces, and TPK district in 120 districts/cities. Information was collected using documentary techniques, focus group discussions, and involved role in the activities. The data analysis technique used, namely description, and interpretation. The study shows that the increase in professional skills (professional development) staff in curriculum development is really a conscious and sustained effort from the leadership of Curriculum Centre. The importance of the creation of a cultural institution with the atmosphere or climate that allows staff to develop, a sound management in strengthening the potential or staff resources and the protection jaminnan staff so that potential can be constructed in a positive and conducive environment which in turn can memandirikan staff in making the work is also a prominent finding in this study. Furthermore, this study also shows that the strategy of empowering the staff at the Curriculum Center is very influential on the successful achievements of technical assistance activities of professional development curriculum to local corruption.Â ABSTRAKKajian yang dikemukakan ini dimaksudkan untuk memperoleh gambaran tentang pemberdayaan staf Pusat Kurikulum melalui strategi kegiatan bantuan teknis profesional pengembangan kurikulum di daerah. Metode kajian ini yaitu deskriptif, di mana data utama diolah berdasarkan program kegiatan, pelaksanaan kegiatan, dan laporan hasil kegiatan Pusat Kurikulum tahun 2006 s.d. tahun 2010 berkait dengan bantuan teknis profesional pengembangan kurikulum kepada TPK provinsi di 33 provinsi, dan TPK kabupaten/kota di 120 kabupaten/kota. Informasi dikumpulkan dengan menggunakan teknik dokumentasi, diskusi terfokus secara kelompok. Teknik analisis data yang dipergunakan, yaitu deskripsi, dan interpretasi. Hasil kajian menunjukkan bahwa peningkatan kemampuan profesional staf dalam pengembangan kurikulum merupakan usaha sadar dan berkesinambungan dari pimpinan Pusat Kurikulum. Pentingnya penciptaan suatu budaya kelembagaan dengan suasana atau iklim yang memungkinkan staf berkembang secara sehat dalam manajemen yang memperkuat potensi staf dan adanya jaminan perlindungan. Dengan demikian, potensi staf dapat dibangun secara positif dan kondusif yang pada gilirannya bisa memandirikan staf dalam berkarya. Kajian ini menunjukkan juga bahwa strategi pemberdayaan staf di tingkat Pusat Kurikulum sangat berpengaruh terhadap capaian keberhasilan kegiatan bantuan teknis profesional pengembangan kurikulum kepada TPK daerah.